Hip Resurfacing. Case presentation. - Pedro Gonzalo González González; Edgar Antezana Bilbao; Tamara Elizabeth Morales Perez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2008)
Hip resurfacing in youngest patients is an excellent surgical technique for Avascular Necrosis compare with a traditional Total Hip Replacement. Report about a 21 years old female patient involved in a car accident in February 2004 with Fracture of the neck of femur treated with compression hip screw Richard's type. Two years later the patient was diagnose with avascular necrosis of the contra lateral hip. Hip resurfacing Metal-Metal was carry out in the above mentioned patient.